BACTERIAL CONTAMINATION OF DRINKING WATER IN SOME POULTRY FARMS IN KHARTOUM STATE - K.Ahmed, Selma; E. Mohamed, Tawfig (Journal of Veterinary Medicine and Animal Production, 2022)
This study was conducted to evaluate the bacterial contamination of drinking water in poultry farms in Khartoum State. Ten farms were investigated. Three samples were taken from each farm; from the main source of water, from the storage place of water and from the poultry drinkers, making a total of thirty. All samples were examined for viable bacteria count and Multiple Tube Fermentation Technique for total coli form bacteria. The mean viable count for the samples taken from the main source was 4.4 ×105; from the storage place of water was 3.2×107, and from the drinkers was 6.6×107. 93% of the samples examined were positive for the Multiple Tube Fermentation Technique for total coli forms